Quantitative analysis of minor and trace elements in blood serum of dairy cattle (Bos taurus) by WDXRF - Natália Carrillo Gaeta; Daniel Ubriaco Oliveira Gonçalves de Carvalho; Mario Augusto Reyes Alemán; Jeferson Silva Carvalho; Patrícia Cedraz; João Cristiano Ulrich; Luigi Jovane; Lilian Gregory; Marcos Antonio Scapin (Brazilian Journal of Radiation Sciences, 2022)
Assessment of heavy metal content in biological fluids is essential to determine human and animal health as a result of exposure to contaminated environments, food, and water. WDXRF is a non-destructive method that involves no chemical treatments. It is possible to perform fast chemical analysis without producing hazardous waste and uses a small sample volume (± 50 mL), which is useful to veterinary usage. Therefore, the aim of this work was to implement an alternative method for minor and trace elements in blood serum samples of dairy cattle (Bos taurus) using WDXRF. It was implemented for the determination of Al, Cr, Co, Fe, Cu, As, and Hg, and the method was evaluated by comparing WDXRF and ICP-OES results of a set of 14 blood serum samples of dairy cattle using principal component analysis (PCA). Results of WDXRF and ICP-OES were statistically equivalent to all analyzed elements, except for Fe and Al, which were still comparable. WDXRF proved to be a suitable alternative methodology for heavy metal detection in animal blood serum samples due to the low sample volume. The results of this study enable a new and fast method for veterinary internal medicine, which requires a technique that quickly detects animals with a high concentration of toxic elements to assure the correct protocols to prevent the animal's death.